2011
DOI: 10.1007/s11427-011-4142-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pns12 as the second silencing suppressor of Rice gall dwarf virus

Abstract: RNA silencing is a conserved mechanism found ubiquitously in eukaryotic organisms. It has been used to regulate gene expression and development. In addition, RNA silencing serves as an important mechanism in plants' defense against invasive nucleic acids, such as viruses, transposons, and transgenes. As a counter-defense, most plants, and some animal viruses, encode RNA silencing suppressors to interfere at one or several points of the silencing pathway. In this study, we showed that Pns12 of RGDV (Rice gall d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…RSV has 4 single standard genomic RNA which is called as RNA1, 2, 3 and 4 with their size in reducing style. RNA1 has one big ORF which encodes a protein of 337 kDa molecular weight that was thought to be Also, Pns12 is localized in the nucleus of N. benthamiana leaf cells [104].…”
Section: Role Of Pc4 As Putative Movement Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…RSV has 4 single standard genomic RNA which is called as RNA1, 2, 3 and 4 with their size in reducing style. RNA1 has one big ORF which encodes a protein of 337 kDa molecular weight that was thought to be Also, Pns12 is localized in the nucleus of N. benthamiana leaf cells [104].…”
Section: Role Of Pc4 As Putative Movement Proteinmentioning
confidence: 99%
“…Eukaryotes and plants use a much-conserved mechanism RNA silencing as a defense strategy against transposons and viruses [104]. Generally, dsRNAs trigger RNA silencing.…”
Section: Transgenic Mechanism As Silencing Suppressormentioning
confidence: 99%
“…Studies of viral counter-defense measure led to the discovery of viral suppressors of RNA silencing. These suppressors not only facilitate our better understanding of RNA silencing pathway [43][44][45], but also serve to increase foreign protein production in transgenic plants [46].…”
mentioning
confidence: 99%
“…Deregulation of miRNA expression has also been implicated in many diseases including cancer. Recent evidence has clearly demonstrated that, other than abnormal epigenetic modifications, dysregulation of miRNA expression may also contribute to aberrant activation of oncogenes, accompanied by inactivation of tumor suppressor genes [20][21][22][23][24].…”
mentioning
confidence: 99%